Capture of zooplankton by site-attached fish: striking dynamics under different flow speeds and prey paths - Ella, Hadar; Genin, Amatzia (Frontiers in Marine Science, 2024)
Consumption of pelagic zooplankton plays a vital role in the functioning of benthic communities such as coral reefs and kelp forests. Many fish that consume zooplankton in those habitats are site attached, foraging for drifting prey while maintaining a fixed position close to a shelter such as a branching coral or a perforated rock. Therefore, the flow, in which their planktonic prey drifts, is expected to affect their foraging movements. However, most attributes of those movements are poorly understood- a gap that our study seeks to fulfil. Our experiments were carried out in a laboratory flume with 4 common coral-reef site-attached species. Their movements were recorded in 3D, using two orthogonal video cameras. Different fishes exhibited similar trends despite noticeable differences in their body size, their morphology, the type of shelters they use, and the typical size of the groups in which they reside. In all species, the strike distance decreased with increasing flow speed. Similarly, the distance between the fish and prey at the moment of strike initiation (“Reactive Distance”) decreased with increasing flow speed, as well as the angle between that “Reactive Distance” and flow direction. Surprisingly, striking speeds (relative to Earth) remained nearly unchanged under different flows speeds. However, faster strikes occurred when oriented at wider angles relative to the flow. Taken together, the fish appear to determine the speed and angle of their strikes based on a cognitive ability to assess the prey’s drifting speed and path in order to reach on time the intercepting point. A rough estimate of the time it takes the fish to decide on the strike’s orientation and speed, would suggest a few hundred of milliseconds. Using published data on the fishes’ feeding rates, we found that the fish significantly differed in their feeding efficiencies, defined as the percent of prey they captured from those passing through their actual foraging space. That difference may explain inter-specific differences in the habitats the fish use and their group size.